Inter- and intraspecific variability as a basis for defining the quality of herbal drug - Marčetić, Mirjana (Archives of Pharmacy, 2022)
To define new herbal drug and its quality, it is important to know inter- and intraspecific variability of chemical constituents of certain species of one genus. In the case of potentially new aromatic herbal drugs, among others, variability of essential oils composition is examined. The aim was to investigate interspecific variability of essential oil composition of four Seseli L. species, Apiaceae and intraspecific essential oil variability of selected species S. rigidum Waldst. & Kit. Composition of oils was determined by GC-FID and GC-MS and results were statistically analysed (ANOVA, PCA, CDA, cluster analysis). Antimicrobial (broth-microdilution, checkerboard method), cytotoxic (MTT test, flow cytometry) and genotoxic/antigenotoxic activity (Comet test) of oils of selected populations of S. rigidum were investigated. Significant differences in oils composition of investigated Seseli species were observed. Monoterpene hydrocarbons dominated in oils of aerial parts of S. rigidum and S. gracile Waldst. & Kit. and sesquiterpene hydrocarbons in S. annuum L. and S. tomentosum Vis. Climate had significant influence on composition, higher than population and substrate (serpentine or calcareous). The best antimicrobial activity showed S. rigidum root oil of population with high falcarinol content against Candida albicans and MRSA. Synergistic effect of mentioned oil and antibiotics was observed. Oils of root, aerial parts and fruit showed cytotoxic activity against tumor cells HeLa, LS174 and A549, while genotoxic effects weren’t observed. Oils of S. rigidum aerial parts and fruit manifested antigenotoxic effects. Conducted research indicated the potential of S. rigidum as a source of new herbal medicinal raw materials.